Trade potential in an enlarged European Union: a recent approach - Fontoura, Maria Paula (2010)
This paper aims to evaluate the trade potential of manufactured products between countries belonging to the EU in the threshold of its Eastern enlargement. For this purpose we use a Gravity model which is estimated with a Poisson Pseudo-Maximum Likelihood Method. We extend the specification of the gravity model in order to capture bilateral trade specificities between groups of countries of the enlarged EU, allowing to test the statistical significance of these inter-groups' trade potential. In addition, it includes the Commodity Composition of Trade. The estimated coefficients are used to project exports of each country. We conclude that in 2002 the CEEC as a group had exhausted their export potentialities to the enlarged EU, whereas the same does not apply to its imports from the EU members.